BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU DIET REMAJA AKHIR USIA 18-22 TAHUN PADA KONSUMEN HERBALIFE DI KOTA SEMARANG - Chania Oktrisia; Priyadi Nugraha Prabamurti; Zahroh Shaluhiyah (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Fashion development introduced people to the ideal body shape, one of which is adolescents, the lack of knowledge about dietary behavior can cause the adolescent to behave unhealthy diet. Herbalife products are claimed as safe products that can be maintaining weight. However, still has an adverse side effect if not used as recommended. This study aimed to find out the related factors to diet behavior late adolescent age in a consumer of Herbalife product located in Semarang city. The design of this study was a cross-sectional study with a quantitative research method. The sample of this study is 85 late adolescent which using Herbalife product, the sample was obtained using proportional random sampling. Data collection was conducted by distributing questionnaires through form application. Data analysis was conducted using univariate and bivariate. The result showed that dependent variable related to knowledge (p=0,000), attitude (0,007), BMI (0,000), body dissatisfaction (0,000), frequency use the product (0,003), friends support (0,001), Herbalife coach support (0,000). It can be concluded there is a correlation between people around who have more interaction with late adolescents to the formation of dietary attitudes and behaviors in late adolescence which using Herbalife products located in Semarang city. Therefore, the health workers may develop a prevention program for unhealthy diet behavior in late adolescence by approaching people around who have more interaction with.